Limosilactobacillus reuteri DSM 17938 reverses gut metabolic dysfunction induced by Western diet in adult rats - Abuqwider, Jumana; Di Porzio, Angela; Barrella, Valentina; Gatto, Cristina; Sequino, Giuseppina; De Filippis, Francesca; Crescenzo, Raffaella; Spagnuolo, Maria Stefania; Cigliano, Luisa; Mauriello, Gianluigi; Iossa, Susanna; Mazzoli, Arianna (Frontiers in Nutrition, 2023)
Introduction Microencapsulation of probiotic bacteria is an efficient and innovative new technique aimed at preserving bacterial survival in the hostile conditions of the gastrointestinal tract. However, understanding whether a microcapsule preserves the effectiveness of the bacterium contained within it is of fundamental importance. Methods Male Wistar rats aged 90 days were fed a control diet or a Western diet for 8 weeks, with rats fed the Western diet divided into three groups: one receiving the diet only (W), the second group receiving the Western diet and free L. reuteri DSM 17938 (WR), and the third group receiving the Western diet and microencapsulated L. reuteri DSM 17938 (WRM). After 8 weeks of treatment, gut microbiota composition was evaluated, together with occludin, one of the tight junction proteins, in the ileum and the colon. Markers of inflammation were also quantified in the portal plasma, ileum, and colon, as well as markers for gut redox homeostasis. Results The Western diet negatively influenced the intestinal microbiota, with no significant effect caused by supplementation with free and microencapsulated L. reuteri. However, L. reuteri, in both forms, effectively preserved the integrity of the intestinal barrier, thus protecting enterocytes from the development of inflammation and oxidative stress. Conclusion From these whole data, it emerges that L. reuteri DSM 17938 can be an effective probiotic in preventing the unhealthy consequences of the Western diet, especially in the gut, and that microencapsulation preserves the probiotic effects, thus opening the formulation of new preparations to be able to improve gut function independent of dietary habits.